2008
DOI: 10.1016/j.athoracsur.2008.01.078
|View full text |Cite
|
Sign up to set email alerts
|

Statin Therapy Improves Outcomes After Valvular Heart Surgery

Abstract: Background-The beneficial effects of 3-hydroxy-3-methylglutaryl coenzyme A (HMG Co-A) reductase inhibitors (statins) in patients undergoing coronary artery bypass grafting have been recognized. Reduced mortality rates and clinical events have been demonstrated. These outcomes were examined in patients taking statins who underwent cardiac valve operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…Additional five studies were identified from reference lists of the identified articles and from other databases. Of the 56 potentially relevant articles, 32 were excluded for reasons given in Figure , leaving a total of 24 studies that met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional five studies were identified from reference lists of the identified articles and from other databases. Of the 56 potentially relevant articles, 32 were excluded for reasons given in Figure , leaving a total of 24 studies that met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty one studies reported associations between use of statins and AKI, and 14 studies reported associations between use of statins and AKI requiring RRT. Five studies used RCT design, and the rest applied a cohort design . Only one RCT defined AKI as the primary endpoint.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies suggesting statin-therapy for every patient with aortic stenosis. (Fedoruk et al 2008) However Rossebo et al showed that statin-therapy did not reduce the composite outcome of combined aortic-valve events and ischemic events in AS patients. Statin-therapy resulted in reduced incidence of ischemic cardiovascular events but not events related to aortic-valve stenosis.…”
Section: Statinsmentioning
confidence: 99%
“…Furthermore, statin therapy was associated with reduced total and cardiovascular mortality after valvular heart surgery 10) or coronary artery bypass grafting surgery 11) . However, these studies included patients with and without diabetes.…”
Section: Fig 2 Survival Curves (Cardiac Death) Of Patients With Andmentioning
confidence: 99%